The Role of a Cytokinin Antagonist in the Progression of Clubroot Disease - Bíbová, Jana; Kábrtová, Veronika; Večeřová, Veronika; Kučerová, Zuzana; Hudeček, Martin; Plačková, Lenka; Novák, Ondřej; Strnad, Miroslav; Plíhal, Ondřej (Biomolecules, 2023)
Plasmodiophora brassicae is an obligate biotrophic pathogen causing clubroot disease in cruciferous plants. Infected plant organs are subject to profound morphological changes, the roots form characteristic galls, and the leaves are chlorotic and abscise. The process of gall formation is governed by timely changes in the levels of endogenous plant hormones that occur throughout the entire life cycle of the clubroot pathogen. The homeostasis of two plant hormones, cytokinin and auxin, appears to be crucial for club development. To investigate the role of cytokinin and auxin in gall formation, we used metabolomic and transcriptomic profiling of Arabidopsis thaliana infected with clubroot, focusing on the late stages of the disease, where symptoms were more pronounced. Loss-of-function mutants of three cytokinin receptors, AHK2, AHK3, and CRE1/AHK4, were employed to further study the homeostasis of cytokinin in response to disease progression; ahk double mutants developed characteristic symptoms of the disease, albeit with varying intensity. The most susceptible to clubroot disease was the ahk3 ahk4 double mutant, as revealed by measuring its photosynthetic performance. Quantification of phytohormone levels and pharmacological treatment with the cytokinin antagonist PI-55 showed significant changes in the levels of endogenous cytokinin and auxin, which was manifested by both enhanced and reduced development of disease symptoms in different genotypes.
Keywords: kyseliny indoloctové; Plant Growth Regulators; Cytokinins; PI-55; Arabidopsis; proteiny huseníčku; Indoleacetic Acids; regulátory růstu rostlin; Arabidopsis Proteins; clubroot; Plasmodiophora brassicae; cytokinin; photosynthesis; auxin; cytokininy